Sistem Informasi Kegiatan Penunjang Akademik Mahasiswa Berbasis Desktop - Dewi Sahara Nasution; Faiz Rafdhi (Jurnal CoSciTech (Computer Science and Information Technology), 2020)
As science and technology have grown, the role and use of information technology has become important. In creation of the book activities on the campus of the Jakarta high school administration of information and computers that have been carried out each year, there are some problems with the data of the activities being carried out and the list of students who have followed the activities that have been carried out, so the certificates and schedule of the activities are ineffective and efficient. In constructing student information-support information system at the Jakarta high school for information management and computers muhammadiyah using Visual Basic (vb.net) as the language oh this program and mysql as database. The system development uses the waterfall model with the step-by-step analysis, design system, coding and testing, implementation and maintenance. The study produced a student’a educational information system that could facilitate the activity data input processstudents can be done quickly, accurately and efficiently. The built system may show student’s overall data, which consists of a list of activities, activity activity times, and activities that have been followed.